2016
DOI: 10.3109/0284186x.2016.1161823
|View full text |Cite
|
Sign up to set email alerts
|

Improving the reproducibility of voluntary deep inspiration breath hold technique during adjuvant left-sided breast cancer radiotherapy

Abstract: Background: Adjuvant radiotherapy (RT) of left-sided breast cancer (LSBC) with voluntary deep inspiration breath hold (vDIBH) technique reduces the cardiac dose. In this study, the effect of marker block position and the efficacy of breath hold level (BHL) correction based on lateral kV setup images are evaluated to improve the daily reproducibility. Material and methods: A total of 148 consecutive LSBC patients treated with vDIBH RT were included in this study. The real-time position management (RPM) marker b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Placement of the RPM block directly on the breast or chest wall has been shown to improve breath hold level reproducibility for left‐sided breast cancer DIBH patients . We investigated three specific concerns when placing the RPM external marker block directly on the breast: (a) surface dose effects; (b) system accuracy with lateral block tilt; and (c) optimal block location on the breast surface.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Placement of the RPM block directly on the breast or chest wall has been shown to improve breath hold level reproducibility for left‐sided breast cancer DIBH patients . We investigated three specific concerns when placing the RPM external marker block directly on the breast: (a) surface dose effects; (b) system accuracy with lateral block tilt; and (c) optimal block location on the breast surface.…”
Section: Discussionmentioning
confidence: 93%
“…Erythema commonly occurs following doses of 3000–4000 cGy to the skin; therefore, for a typical breast dose of 5000 cGy placement of the marker block in the primary beam could lead to increased incidence of erythema. There have been two patient studies where the (two‐dot) RPM marker block has been placed in the primary radiation field: one reported that there were no observed skin reactions resulting from the marker block for 31 patients; the other did not report on the incidence of skin reactions …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was likely due to the effect of C‐C breathing motion. If the A‐P BHL is lower than planned, it is more likely that positional errors also occur in the C‐C direction 14. Thus, if in 2D image guidance the match of lateral image is performed with a compromise between the sternum and spine, but prioritizing the sternum, then the C‐C residual error of the spine is likely connected with the altered breathing motion.…”
Section: Discussionmentioning
confidence: 99%